2018
DOI: 10.1021/acs.jced.8b00142
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Carbon Dioxide Solubility in Aqueous N-Methyldiethanolamine Solution with 1-Butylpyridinium Tetrafluoroborate Ionic Liquid

Abstract: New experimental data for CO2 solubility in the aqueous solutions of N-methyldiethanolamine (MDEA) and 1-butylpyridinium tetrafluoroborate ([Bpy]­[BF4]) ionic liquid (IL) are reported. The experiments were conducted in a static high pressure equilibrium cell. Solubility measurement of CO2 was performed in various solution compositions of IL and MDEA in a wide temperature range of 298.15–343.15 K and pressures up to 4 MPa. The experimental results revealed that, by increasing the weight percent of IL, the absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…[31,32], evaluated the use of water as a co-solvent. [14,26,27,33,34] As stated by the authors, the IL-amine hybrid solvents have shown to be, through the manipulation of the IL concentration, an energy-saving system for CO 2 capture with reduced heat of absorption and manageable diffusivities and kinetics. [14] Gómez-Coma et al [13] aiming at enhancing the CO 2 chemisorption, through the optimization of acetate-based ILs, proposed the use of aqueous solutions of 1-ethyl-3methylimidazolium acetate in nondispersive absorption in a polyvinylidene fluoride hollow fiber membrane contactor.…”
Section: Accepted Manuscriptmentioning
confidence: 93%
See 1 more Smart Citation
“…[31,32], evaluated the use of water as a co-solvent. [14,26,27,33,34] As stated by the authors, the IL-amine hybrid solvents have shown to be, through the manipulation of the IL concentration, an energy-saving system for CO 2 capture with reduced heat of absorption and manageable diffusivities and kinetics. [14] Gómez-Coma et al [13] aiming at enhancing the CO 2 chemisorption, through the optimization of acetate-based ILs, proposed the use of aqueous solutions of 1-ethyl-3methylimidazolium acetate in nondispersive absorption in a polyvinylidene fluoride hollow fiber membrane contactor.…”
Section: Accepted Manuscriptmentioning
confidence: 93%
“…[9] At present, the research on ILs mixed solvents for CO 2 capture focus mainly on ILwater solutions, IL-alkanolamine blends, IL-organic solvents and IL-IL mixtures. [13,14,[25][26][27] Although not a trivial task, due to the strong dependence on the nature of the constituents ions/compounds, several authors evaluated mixtures of ILs as a mechanism to increase the sorption capacity by manipulating specific interactions, excess volume and viscosity. As reported by Moya et al.…”
Section: Accepted Manuscriptmentioning
confidence: 99%